Thulium bismuth co-doped fiber lasers at 1901 nm by 802 nm pumping - Halder, Arindam; Saidin, Norazlina; Harun, Sulaiman Wadi; Ahmad, Harith; Paul, Mukul Chandra; Dimyati, Kaharudin; Das, Shyamal; Bhadra, S.K; Zen, D.I.M; Damanhuri, S.S.A (IEEE Photonics Society, 2014)
We demonstrate an efficient fiber laser operating at 1901.6 nm using a new Thulium Bismuth co-doped fiber (TBF) under 802 nm pumping. The TBF was fabricated using modified chemical vapor deposition process associated with optimized solution doping techniques. The TBF lasers at 1901.6 nm are obtained at a noticeably low threshold pump power of 75–92 mW using two fiber Bragg gratings in a Fabry–Perot cavity. The highest efficiency of 42.2% is achieved using a 0.4m long TBF fiber with a core dopant concentrations (in wt%) of 0.35 Bi2O3 , 0.9 Tm2O3 , 3.0 Al2O3 and 4.0 GeO2 . Compared to the laser from a commercially available Thulium-doped fiber, the proposed laser has a significantly higher efficiency and lower threshold pump power. This is attributed to the incorporation of Bi ions in the gain medium which helps to increase the 3F4 population through energy transfer processes. The maximum output power of 52.7mWis achieved at the pump power of 195 mW.